Norway: Wilkins-Hearst Antarctic Expedition 1928-29, men on ice and in cave - Wilkins, George H. (George Hubert), Sir, 1888-1958 (1928)
Wilkins-Hearst Antarctic Expedition 1928-29. Men on ice, showing man in cave.